2020
DOI: 10.1302/0301-620x.102b10.bjj-2020-0138.r1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E-doped total hip arthroplasty liners show similar head penetration to highly cross-linked polyethylene at five years: a multi-arm randomized controlled trial

Abstract: Aims The most frequent indication for revision surgery in total hip arthroplasty (THA) is aseptic loosening. Aseptic loosening is associated with polyethylene liner wear, and wear may be reduced by using vitamin E-doped liners. The primary objective of this study was to compare proximal femoral head penetration into the liner between a) two cross-linked polyethylene (XLPE) liners (vitamin E-doped (vE-PE)) versus standard XLPE liners, and b) two modular femoral head diameters (32 mm and 36 mm). Methods Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…In the same review article, the authors proposed that an even safer threshold of 0.05 mm/year would eliminate osteolysis and the VEPE cup fulfills this requirement as well. These results are consistent with the previously published data on VEPE in uncemented cups (7,8,18,19).…”
Section: Discussionsupporting
confidence: 94%
“…In the same review article, the authors proposed that an even safer threshold of 0.05 mm/year would eliminate osteolysis and the VEPE cup fulfills this requirement as well. These results are consistent with the previously published data on VEPE in uncemented cups (7,8,18,19).…”
Section: Discussionsupporting
confidence: 94%
“…A uniplanar RSA set up was used. This presents the common set up for hip implant migration measurement [34][35][36]. The results of this study showed the reliability of out-of-plane migration measurements was inferior to in-plane migration measurements, which can be a common limitation of the uniplanar calibration set up [14].…”
Section: Discussionmentioning
confidence: 85%
“…From the remaining 56 studies, the reviewers excluded abstracts, reviews, protocols, and animal studies based on the inclusion and exclusion criteria. Finally, 14 studies were included, containing 11 RCTs and 3 case-control studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The flowchart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The flowchart is shown in Figure 1. [17,[19][20][21]25], two studies [16,27] used sealed hidden envelopes for allocation but did not mention specific blinding, and four studies used computer randomized allocation. Study bias was low in these RCTs [22][23][24]26].…”
Section: Resultsmentioning
confidence: 99%